Comparison of GeneXpert cycle threshold values with smear microscopy and culture as a measure of mycobacterial burden in five regional referral hospitals of Uganda- A cross-sectional study - Najjingo, Irene; Muttamba, Winters; Kirenga, Bruce J.; Nalunjogi, Joanitah; Bakesiima, Ritah; Olweny, Francis; Lusiba, Pastan; Katamba, Achilles; Joloba, Moses; Ssengooba, Willy (PLoS ONE, 2019)
Determining mycobacterial burden is important in assessing severity of disease, evaluating infectiousness and predicting patient treatment outcomes. Mycobacterial burden assessed by smear microscopy grade and time to culture positivity is clearly interpretable by most physicians. GeneXpert (Xpert) has been recommended by WHO as a first line tuberculosis (TB) diagnostic test as an alternative to smear microscopy. Xpert gives cycle threshold (Ct) values as a potential measure for mycobacterial burden. For physicians to clearly interpret Ct values as measures of mycobacterial burden, this study compared the Xpert quantification capabilities with those of smear microscopy and culture. The study also determined a linear relationship between Xpert Ct values and MGIT culture time to positivity (MGIT-TTP) and associated factors. A cut off Ct value which best predicts smear positivity was also determined using the Receiver Operator Curve analysis method. Results Excluding missing results and rifampicin resistant TB cases, a moderately strong correlation of 0.55 between Xpert Ct value and smear grade was obtained. A weak correlation of 0.37 was obtained between Xpert Ct values and MGIT time to positivity while that between Xpert Ct values and LJ culture was 0.34. The Xpert Ct values were found to increase by 2.57 for every unit increase in days to positive and HIV status was significantly associated with this relationship. A cut off Ct value of 23.62 was found to best predict smear positivity regardless of HIV status. Conclusion Our study findings show that GeneXpert Ct values are comparable to smear microscopy as a measure of M. tuberculosis burden and can be used to replace smear microscopy. However, given the low correlation between Xpert Ct value and culture positivity, Xpert Ct values cannot replace culture as a measure of M. tuberculosis burden among TB patients.
Keywords: GeneXpert cycle threshold; Smear microscopy; Culture; Mycobacterial burden